Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.7759/cureus.7232
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Cerebral Palsy Among Sudanese Children Less Than 15 Years of Age

Abstract: Background: Cerebral palsy (CP) is a non-progressive, everlasting neurological disorder of movement, posture, and physical activities, with a prevalence of 2.2-3.3/1,000. CP is a condition that occurs globally, with a similar prevalence in both developed and undeveloped countries. However, the etiology differs according to the socioeconomic status of the countries. The objective is to determine the pattern and the contributing factors of CP among Sudanese children. Methods: This was a retrospective hospital-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Most of the studies were from Saudi Arabia ( n = 10) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], Jordan ( n = 8) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], Egypt ( n = 6) [ 47 , 48 , 49 , 50 , 51 , 52 ], and Iraq ( n = 4) [ 53 , 54 , 55 , 56 ]. Other studies were from Sudan ( n = 2) [ 57 , 58 ], Libya ( n = 1) [ 59 ], and Palestine ( n = 1) [ 60 ]. There were a variety of study designs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies were from Saudi Arabia ( n = 10) [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], Jordan ( n = 8) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], Egypt ( n = 6) [ 47 , 48 , 49 , 50 , 51 , 52 ], and Iraq ( n = 4) [ 53 , 54 , 55 , 56 ]. Other studies were from Sudan ( n = 2) [ 57 , 58 ], Libya ( n = 1) [ 59 ], and Palestine ( n = 1) [ 60 ]. There were a variety of study designs.…”
Section: Resultsmentioning
confidence: 99%
“…Most were of case-series ( n = 13) [ 32 , 33 , 34 , 36 , 38 , 40 , 41 , 42 , 43 , 44 , 53 , 55 , 56 ] and cross-sectional design ( n = 11) [ 29 , 31 , 39 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Other study designs included: case-control ( n = 5) [ 35 , 54 , 58 , 59 , 60 ], retrospective review ( n = 2) [ 37 , 57 ], and prospective/retrospective cohort ( n = 1) [ 30 ]. Seven studies [ 31 , 46 , 47 , 48 , 49 , 50 , 52 ] reported comparable prevalence; however, only one study reported birth years [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cans et al (2004) reported that 50% of cases of cerebral palsy with postneonatal origin (arising more than 28 days after birth, and before the age of 25 months) were caused by infection;20% caused by vascular episodes, 18% caused by head injury. They suggested that children with cerebral palsy of post-neonatal origin had a more severe functional pattern than non-post-neonatal cerebral palsy children [19]. Reid and colleagues (2006) from Australia reported that 10.7% of 339 cases of cerebral palsy had post-neonatally acquired condition caused by infection, traumatic head injury a, hypoxia, acute encephalopathies, and cerebrovascular accidents [20].…”
Section: Discussionmentioning
confidence: 99%
“…The work of Salih (2020) from Sudan emphasized that prenatal causes were the most common causes of cerebral palsy, but post natal causes included neonatal jaundice and acquired sepsis [21].…”
Section: Discussionmentioning
confidence: 99%